Memories to assemble. The commemorations of the March 24, on primary schools located near of Buenos Aires (Quinto Sol, 2011)
This article focuses on the problem of the approach to the recent past in schools. It describes the different representations of the military dictatorship in the speeches made in 2008 to remember the coup d’etat of 24 March 1976 in the Malvinas Argentinas party, located near Buenos Aires. The presence of different narrations from the collective memory is analyzed in those speeches.
Keywords: School; military dictatorship; recent past; collective memory